Experiences and Perspectives of Medication Information and Use Among Arabic-Speaking Migrant Women in Sweden: A Multistage Focus Group Study - Al Musawi A; Axelsson M; Eriksson T; Rämgård M (Patient Preference and Adherence)
Ahmed Al Musawi,1 Malin Axelsson,2 Tommy Eriksson,1 Margareta Rämgård2,3 1Department of Biomedical Science and Biofilm – Research Centre for Biointerfaces, Malmö University, Malmö, Skåne, Sweden; 2Department of Care Science, Malmö University, Malmö, Skåne, Sweden; 3Research Centre Promoting Citizen Health Through Collaborative Practices, Malmö University, Malmö, Skåne, SwedenCorrespondence: Ahmed Al Musawi, Department of Biomedical Science and Biofilm – Research Center for Biointerfaces, Malmö University, Jan Waldenströms gata 25, Malmö, Skåne, 205 06, Sweden, Email ahmed.almusawi@mau.sePurpose: Medication non-adherence is a global public health issue influenced by various factors, including the quality and comprehensiveness of medication information provided to patients. Migrants, particularly women, face unique healthcare and societal challenges in their new home countries. This study aims to explore Arabic-speaking migrant women’s experiences and perspectives on medication information and use.Methods: This study was part of the Equal Health program, a health promotion initiative established in socially vulnerable areas to address health inequities. Arabic-speaking women aged 40– 80 years with chronic illnesses participated in multistage focus group sessions exploring their experiences with medication information from healthcare, medication use, and perspectives on necessary improvements in medication information at hospital discharge. The sessions were conducted in Arabic, audio-recorded, transcribed verbatim, and translated into Swedish for analysis. Data were analyzed using Braun and Clark’s six-phase reflexive thematic analysis.Results: Four multistage focus group sessions with 15 participants were conducted. The analysis generated three themes: receiving or not receiving professional medication information, medication adherence patterns, and needs and suggestions for improved medication information—a call for action. Participants reported inadequate medication information from physicians, particularly at the time of discharge from the hospital, and described instances of intentional and unintentional non-adherence. Suggestions for improvement included providing written medication information at discharge in their native language, using interpreters, and including a current medication list detailing overall medication information and potential drug interactions.Conclusion: This study highlights inadequate medication information provision to Arabic-speaking migrant women, which may impact medication use and pose patient safety risks. Although the adherence patterns of the study subjects resembled those of the general population, unique barriers require additional healthcare support. This study can inform healthcare practices and establish a foundation for further research on medication information and use in this group, including comparisons with native-born individuals.Keywords: medication adherence, migrant health, health equity, vulnerable population, health perception